(untitled) (Revista INTEREDU11, 2024)
The objective of this research is to describe the technological resources present in Chilean textbooks for the teaching of mathematics in Primary Education in the subjects of statistics and probability. To achieve this objective, qualitative research was carried out, using the content analysis method. A total of 24 textbooks were analyzed, three per course (student’s text, teacher’s guide and exercise book), from 1st to 8th grade of Primary Education. Among the results, it is highlighted that the technological resources are focused on the final courses (7th and 8th), the most frequent being the learning guides. In addition, a significant number of resources that do not work or are not available were observed. It is concluded that there is a need to increase the variety and number of technological resources that support the teaching and learning processes of statistics and probability.